Reporting results from whole-genome and whole-exome sequencing in clinical practice: a proposal for Canada?. Issue 1 (27th September 2013) - Zawati, Ma'n H; Parry, David; Thorogood, Adrian; Nguyen, Minh Thu; Boycott, Kym M; Rosenblatt, David; Knoppers, Bartha Maria
Abstract : Purpose: This article proposes recommendations for the use of whole-genome and whole-exome (WGS/WES) sequencing in clinical practice, endorsed by the board of directors of the Canadian College of Medical Geneticists. The publication of statements and recommendations by several international and national organisations on clinical WGS/WES has prompted a need for Canadian-specific guidance. Methods: A multi-disciplinary group consisting of lawyers, ethicists, genetic researchers, and clinical geneticists was assembled to review existing guidelines on WGS/WES and identify provisions relevant to the Canadian context. Results: Definitions were provided to orient the recommendations and to minimize confusion with other recommendations. Recommendations include the following: WGS/WES should be used in a judicious and cost-efficient manner; WGS/WES should be used to answer a clinical question; and physicians need to explain to adult patients the nature of the results that could arise, so as to allow them to make informed choices over whether to take the test and which results they wish to receive. Recommendations are also provided for WGS/WES in the pediatric context, and for when results implicate patients' family members. Conclusion: These recommendations are only a proposal to be developed into comprehensive Canadian-based guidelines. They aim to promote discussion about the reporting of WGS/WES results, and to encourage the ethical implementation of these new technologies in the clinical setting.